2006
DOI: 10.1300/j184v09n04_02
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Biofeedback in the Treatment of Attention-Deficit/Hyperactivity Disorder

Abstract: Historically, pharmacological treatments for attentiondeficit/hyperactivity disorder (ADHD) have been considered to be the only type of interventions effective for reducing the core symptoms of Vincent J. Monastra is affiliated with the FPI Attention Disorders Clinic, Endicott, ). Each paper in this series has been reviewed and approved by the Series editors, and by the Boards of Directors of both ISNR and AAPB. Each white paper in the series stands as an official association statement on an application area o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 71 publications
1
24
0
1
Order By: Relevance
“…Majority of the children with ADHD (85%-90%) has EEG under activity with elevated relative theta power, reduced relative alpha, and beta power, and elevated theta/alpha and theta/beta power ratios. 17,18 A smaller group of children has a surplus of beta1 activity and decreased alpha activity. Another endophenotype of ADHD shows EEG patterns similar to younger subjects commonly known as "maturation lag."…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Majority of the children with ADHD (85%-90%) has EEG under activity with elevated relative theta power, reduced relative alpha, and beta power, and elevated theta/alpha and theta/beta power ratios. 17,18 A smaller group of children has a surplus of beta1 activity and decreased alpha activity. Another endophenotype of ADHD shows EEG patterns similar to younger subjects commonly known as "maturation lag."…”
Section: Introductionmentioning
confidence: 99%
“…Theta/beta NFT protocol is administered based on the "under-arousal hypothesis," that is, children with ADHD has elevated relative theta power and reduced relative beta power. 18 EEG NFT reinforces the child to inhibit theta waves and to increase beta/SMR (sensorimotor rhythm) in the frontal region of the brain, which is associated with higher cortical arousal and inhibition of involuntary motor activity. Based on this rationale, numerous studies have been conducted to explore the efficacy of NFT in the treatment of ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, beta EEG activity has been implicated in attentional processing, much of which is based on attempts to normalise the EEG of those with attentional dysfunction (see e.g., Lubar, Swartwood, Swartwood & O'Donnell, 1995;Lubar, Swartwood, Swartwood & Timmerman, 1995). Support for this comes from research focusing on enhancing beta power using EEG biofeedback which has been shown to improve attentional processing in both clinical populations (Fuchs et al, 2003;Monastra et al, 2006) and healthy participants (Egner & Gruzelier, 2004;Rasey et al, 1996). In addition, research has shown increases in beta (12-30Hz) amplitude when participants attend to a stimulus and plan a response (Saleh, Reimer, Penn, Ojakangas & Hatsopoulos, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…According to some studies, antisocial and criminal behavior is associated with attention deficit, learning problems, and impulsivity (Barkley, 1997). One method that has been utilized is neurofeedback (NFB) training (Monastra et al, 2006); however, at the present time there is not much information about the effects of this procedure in adolescents in conflict with the law, nor information about the impact of the NFB in this population in Mexico.…”
Section: Effects Of Neurofeedback Training In a Group Of Adolescents mentioning
confidence: 99%